5x - 4 = 3x + 6 5x - 3x = 6 + 4 2x = 10 x = 5
If x=6 and y=8, then [ 5x + 8y ] = 5(6) + 8(8) = 30 + 64 = 94
45
The solutions to the quadratic equation are: x = -1 and x = 6
y = 5x - 4 Substitute 6 in for y; then solve for x: 6 = 5x -4 10 = 5x 2 = x So, the x-coordinate is 2.
-5x+2=-6+x therefore -5x+2+6=x therefore 2+6=x+5x therefore 8=6x therefore 8/6=x therefore x=4/3=1.3333
5x+1+x-2 = 8x+6 5x+x-8x = 6+2-1 -2x = 7 x = -3.5
45
x = −5X + 6
x=1 2/3 How?: 2x-4+3 = 5x-6 2x-1 = 5x-6 2x-1+1 = 5x-6+1 2x = 5x-5 2x-5x = 5x-5x-5 -3x = -5 -3x/-3 = -5/-3 x = 5/3 x = 1 2/3
2x2 - 5x + 6 = ?x = -1(2 x (-1)2) - (5 x -1) + 6 = ?(2 x 1) - (-5) + 6 = ?2 + 5 + 6 = 13
The answer is 79. Since you know the values of x and y, you can simply substitute them into the equation to find the answer. x = 6 y = 7 5x + 7y = 5(6) + 7(7) = 30 +49 = 79
Then x = 6 Therefore; 5x + 3 = 33 First you have to solve the value of X: 8X + 5X + 2X +4X = 114; OR 19x = 114. When you divide both sides of the equation by 19 to solve for X, you find that X = 6. Ergo, 5X + 3 = 30 + 3 = 33; hence, 5X + 3 = 33.
3/5x + 22 = 28 To solve this: Subtract 22 from both sides: 3/5x = 6 Multiply by 5x: 3 = 6*5x Divide by 6: 3/6 = 5x Divide by 5: (3/6)/5 = x Work it out: 3/6 = 0.5 0.5/5 = 0.1 x = 0.1
X=5
128
X=122.2